Integrating Health Education and Holistic Nursing (Acupressure and Hydrotherapy) to Improve Knowledge and Clinical Outcomes of Hypertension and Joint Pain - Liyanti; Fatimah; Muhammad Noorhadi; Muhammad Busyairi; Rabiatul Adawiyah; Meti Agustini (OMNICODE Journal (Omnicompetence Community Developement Journal), 2026)
Hypertension and joint pain are prevalent comorbidities affecting both the productive age and elderly populations in Barikin Village, primarily driven by sedentary lifestyles and limited health literacy. This community service aimed to improve the community's health status and knowledge regarding independent disease management through an integrated approach. The program involved 30 participants and was conducted in two main phases: 1) Interactive health education (counseling) to boost cognitive understanding, and 2) holistic nursing interventions consisting of infused water provision, acupressure, and warm water foot soaks. The implementation utilized interactive lectures, pre-test and post-test knowledge evaluations using validated questionnaires, and direct demonstrations of complementary therapies. The results indicated a significant increase in participants' knowledge regarding hypertension and joint pain management (scores increased from 69.70 to 81.17). Furthermore, clinical observations showed a general trend of decreased systolic blood pressure and significantly reduced pain scales immediately following the complementary therapies. The integration of structured health education and non-pharmacological holistic interventions effectively empowers the community to manage their cardiovascular and musculoskeletal health independently.